2023
DOI: 10.1001/jamacardio.2022.5320
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Personalized Accelerated Pacing on Quality of Life, Physical Activity, and Atrial Fibrillation in Patients With Preclinical and Overt Heart Failure With Preserved Ejection Fraction

Abstract: ImportancePatients with heart failure with preserved ejection fraction (HFpEF) with a pacemaker may benefit from a higher, more physiologic backup heart rate than the nominal 60 beats per minute (bpm) setting.ObjectiveTo assess the effects of a moderately accelerated personalized backup heart rate compared with 60 bpm (usual care) in patients with preexisting pacemaker systems that limit pacemaker-mediated dyssynchrony.Design, Setting, and ParticipantsThis blinded randomized clinical trial enrolled patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
47
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 51 publications
1
47
0
Order By: Relevance
“…The current report demonstrates how a moderately sized but well-executed trial can provide definitive results that disprove conventional paradigms and should prompt reconsideration of current clinical management guidelines. There are other ongoing pacing trials in HFpEF (NCT04546555; NCT03338374), and a recent trial suggested benefit from a higher backup pacing rate among patients with subclinical or overt HFpEF who already had pacemaker implantation for other indications . However, a recent meta-analysis of pacing for heart failure supports the results of the presently reported trial, furthering the case for abandoning rate-adaptive pacing for most patients with HFpEF, despite their chronotropic incompetence.…”
mentioning
confidence: 73%
“…The current report demonstrates how a moderately sized but well-executed trial can provide definitive results that disprove conventional paradigms and should prompt reconsideration of current clinical management guidelines. There are other ongoing pacing trials in HFpEF (NCT04546555; NCT03338374), and a recent trial suggested benefit from a higher backup pacing rate among patients with subclinical or overt HFpEF who already had pacemaker implantation for other indications . However, a recent meta-analysis of pacing for heart failure supports the results of the presently reported trial, furthering the case for abandoning rate-adaptive pacing for most patients with HFpEF, despite their chronotropic incompetence.…”
mentioning
confidence: 73%
“…In Reply We thank Camilli and colleagues for their interest in the myPACE trial . We agree that the reduction in atrial fibrillation (AF) with moderately accelerated pacing in patients with heart failure with preserved ejection fraction (HFpEF) requires further study and confirmation.…”
mentioning
confidence: 95%
“…In contrast, the recently published myPACE study randomized 107 patients with HFpEF (ejection fraction >50%) and an existing pacemaker to a nominal lower rate or a personalized lower rate . Patients were not required to have chronotropic incompetence or to be programmed with rate-adaptive atrial pacing.…”
mentioning
confidence: 99%